CGRP as a Biochemical Biomarker in Migraine Diagnosis: A Systematic Review - Różycka, Karolina; Krycia, Kamila; Mulawa, Magdalena; Mazur, Karolina; Gałuszka, Aleksandra; Piaszczyńska, Emilia; Matacz, Dominika; Drabik, Sandra; Gałuszka, Maja; Adamczyk, Adrianna (Journal of Education, Health and Sport, 2026)
Introduction. Migraine is one of the leading causes of disability worldwide, particularly among young women. Due to the key role of calcitonin gene-related peptide (CGRP) in the activation of the trigeminovascular pathway, this molecule has emerged as a major candidate for a biochemical marker that could facilitate precise diagnosis and classification of patients. Aim. The aim of this review is to systematize the most recent evidence regarding the potential of CGRP as a diagnostic biochemical biomarker of migraine. Methods. The study was conducted in accordance with PRISMA guidelines, with a systematic search of MEDLINE, Web of Science, and Embase databases for publications from the last six years. A total of 166 records were identified, of which 13 articles were included in the final analysis following rigorous selection. Results. Most of the analyzed studies confirm that CGRP levels are significantly elevated in patients with migraine, particularly during the ictal phase. This has been demonstrated in serum, plasma, saliva, and tear fluid. CGRP levels were found to correlate with pain intensity and the severity of clinical symptoms. Higher concentrations were observed in chronic migraine (CM) compared to episodic migraine (EM). However, findings regarding interictal levels remain inconsistent, with some studies showing no significant differences between patients and healthy controls. Conclusions. CG RP remains a promising, yet still imperfect, diagnostic biomarker. Its clinical utility is limited by considerable methodological heterogeneity and the influence of individual factors such as sex, age, and comorbidities.